2008
DOI: 10.1007/s00221-008-1617-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of configural distortion on a face-related ERP evoked by random dots blinking

Abstract: Using random dots blinking (RDB), which reflects the activity of the higher visual area related to face perception, the following stimuli were presented. (1) Upright: a schematic face; (2) Inverted: the Upright stimulus inverted; and (3) Scrambled: the same contour and features as in Upright but with the spatial relation distorted. Clear negative components (N-ERP250) were identified at approximately 250 ms after stimulus onset. At the T5 and T6 electrodes, the peak latency was significantly longer for Inverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
0
6
1
Order By: Relevance
“…In a previous study using RDB ( Okusa et al, 1998 ; Okusa et al, 2000 ), a clear evoked component peaking at around 200–300 msec was identified. In this study ( Miki et al, 2009 ), we identified a component that had a peak deflection 200–300 msec after stimulus onset at T5 and T6 electrodes of the International 10–20 System in the left and right temporal areas, respectively. The peak latency when the amplitude of the component was maximal for each condition after the stimulus onset and the maximum amplitude of the component were individually measured within 300 msec.…”
Section: A Useful Visual Stimulus Methods For Investigating Face Perc...mentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study using RDB ( Okusa et al, 1998 ; Okusa et al, 2000 ), a clear evoked component peaking at around 200–300 msec was identified. In this study ( Miki et al, 2009 ), we identified a component that had a peak deflection 200–300 msec after stimulus onset at T5 and T6 electrodes of the International 10–20 System in the left and right temporal areas, respectively. The peak latency when the amplitude of the component was maximal for each condition after the stimulus onset and the maximum amplitude of the component were individually measured within 300 msec.…”
Section: A Useful Visual Stimulus Methods For Investigating Face Perc...mentioning
confidence: 99%
“…We investigated the face perception process using the RDB method in ten normal adult subjects with normal or corrected visual acuity ( Miki et al, 2009 ). We presented visual stimuli using RDB.…”
Section: A Useful Visual Stimulus Methods For Investigating Face Perc...mentioning
confidence: 99%
See 3 more Smart Citations